Ensino em grupo de habilidades sociais para pessoas com autismo: uma revisão da literatura - Andreozzi, Giovanna Cecília Santoro Frota Pagano (2017)
Although there is a wide variety of applied research and literature reviews on social skills, the multiplicity of evaluation measures and factors used to characterize these studies make it difficult to analyze and compare the variables related to their positive outcomes. The present study updated and analyzed the data from reviews and meta-analysis published from 2006 to 2017, in order to systematize the characteristics of research related to positive results on teaching social skills in groups, for people with ADS. The search conducted on EMBASE, ERIC, MEDLINE and PsycINFO databases resulted in 47 studies published between 2006 and 2017. Aspects not covered by previous reviews (and/or unsystematically covered) were analyzed. The results evidenced a period of few publications on North American and other countries publications in 2014, however, after 2015 a new period of acceleration was observed for non-US publications. Most of the selected studies were published in journals with an impact factor between three and four. Participants were mostly arranged in groups with more than six children diagnosed with Autism, with a multiplicity of secondary diagnoses and IQ greater than 70. The cognitive behavioral approach was the most used and the teaching sessions, for the most part, consisted of at least one-hour meetings, were conducted by therapists, were held once a week and totalled 10 to 20 sessions. Most of the encounters lasted for at least an hour, took place once a week, and ranged from 10 to 20 sessions. Few reviewed studies involved parent training and less than half planned generalization, however, when planned, focused only on other settings and people. The most trained target behavior was to initiate and / or maintain a conversation and the teaching procedures used most frequently, according to the authors, was the behavioral rehearsal and the feedback and the most frequent limitations were procedural methodological limitations. More than half of the interventions were considered effective by the authors, however, the most used follow up was an interval of only three to six months. It was concluded that, for the authors, 47 of the results could be considered effective or partially effective, although there were limitations regarding the planning of generalization of the target behavior and the measure of its maintenance after the end of the intervention. It is suggested that more studies be developed with greater methodological control of the procedures, better characterization of the participants and their initial repertoires, better definition of the procedures used, a topographical description of the target behavior of the intervention and, if possible, future researchers in the area of HS can fill the gaps pointed to provide a consistent basis for group teaching of HS for people diagnosed with ASD